Uveitis and Myositis as Immune Complications in Chemorefractory NK/T-Cell Nasal-Type Lymphoma Successfully Treated with Allogeneic Stem-Cell Transplant - Maria José Gómez-Crespo; Aránzazu García-Raso; Jose Luis López-Lorenzo; Teresa Villaescusa; María Rodríguez-Pinilla; José Fortes; Cristina Serrano; Salma Machan; Pilar Llamas; Raúl Córdoba (Case Reports in Hematology)
NK/T-cell lymphomas are a group of clonal proliferations of NK- or, rarely, T-cell types and have peculiar clinicopathologic features. Most common site of involvement is the upper aerodigestive tract (nasal cavity, nasopharynx, paranasal sinuses, and palate). Association of autoimmune paraneoplastic disorders with NK/T-cell lymphomas is not well studied. Our patient was diagnosed with NK/T-cell lymphoma stage IV with skin involvement and treated frontline with CHOEP regimen. While he was under treatment, two immune complications presented: anterior uveitis of autoimmune origin refractory to steroids and myositis in lower limbs muscles. Autologous transplantation was rejected due to confirmed early relapse after first-line treatment, and the patient received second-line treatment according to the SMILE scheme, reaching complete response after four cycles. The patient underwent allogeneic transplantation and at the time of manuscript preparation is alive despite multiple complications. The disease should be suspected in patients with rhinitis or recurrent sinusitis, and early biopsy is recommended for all patients to avoid a delay in diagnosis. Our patient also presented symptoms of disease progression after first-line treatment, representing a paraneoplastic process, a very rare phenomenon in T-type lymphomas. This case is novel for the appearance of an inflammatory myositis, a histologically verified paraneoplastic phenomenon that responded to treatment for lymphoma.